Differences in Laryngeal Neurotrophic Factor Gene Expression after Recurrent Laryngeal Nerve and Vagus Nerve Injuries. (October 2013) - Halum, Stacey L.; Bijangi-Vishehsaraei, Khadijeh; Saadatzadeh, M. Reza; McRae, Bryan R.
Objectives: Recurrent laryngeal nerve (RLN) and vagus nerve (VN) injuries characteristically are followed by differing degrees of spontaneous reinnervation, yet laryngeal muscle neurotrophic factor (NF) expression profiles after RLN and VN injuries have not been well elucidated. This study's objective was to determine the relative changes in gene expression of 5 well-characterized NFs from laryngeal muscle after RLN or VN injuries in a time-dependent fashion, and demonstrate how these changes correspond with electromyography-assessed innervation status. Methods: Thirty-six male rats underwent left RLN transection (12 rats), left VN transection (12 rats), or a sham procedure (12 rats). The primary outcomes included electromyographic assessment and laryngeal muscle NF expression quantification with reverse transcription polymerase chain reaction at 3 days and at 1 month. Results: Electromyography at 3 days demonstrated electrical silence in the VN injury group, normal activity in the sham group, and nascent units with decreased recruitment in the RLN injury group. Reverse transcription polymerase chain reaction demonstrated that changes in NF gene expression from laryngeal muscles varied depending on the type of nerve injury (RLN or VN) and the specific laryngeal muscle (posterior cricoarytenoid or adductor) assessed. Conclusions: Laryngeal muscle NF expression profiles after cranial nerve X injury depend both upon the level of nerve injury and upon the muscles involved.